Stemming Algorithm Modification for Overstemming Cases - Stephanie Betha R.H. (Universitas Pendidikan Indonesia, 2023)
The stemming process plays an important role in the preprocessing of the text. One of the problems that occur in the stemming process is overstemming. Overstemming is an exaggerated word cut causing situations where a word has a very different meaning, but it produces the same stem. Therefore, to overcome these problems, it will be modified on the stemming process. This modification is done by combining two stemming algorithms (hybrid stemming) that is the look-up algorithm of dictionary table and affix removal algorithm using stemming porter. The modification of this stemming algorithm will be tested on title in scientific publication documents. The test results show that stemming process with modification of stemming algorithm can increase the recall value in the title attribute, although not very significant. The recall in an experiment using title attribute is 89,9%.